Accepting the future as ever-changing: professionals' sensemaking about artificial intelligence. Issue 1 (3rd January 2022) - Goto, Masashi
Abstract: This article examines how professionals leading the digitalization of professional service firms construct their views on new digital technologies such as artificial intelligence (AI) and the influence of such technologies on their future. This understudied question is important because such early-stage envisioning can significantly affect the later processes and outcomes of digitalization. A qualitative study was conducted, using interview and archival data, on a Big Four audit firm in Japan during the period 2017–9, when its taskforce considered applying AI to its core audit service. The contribution of this study is threefold. First, the findings expand our knowledge of prospective sensemaking by introducing a distinct mode of viewing the future that accepts the future as ever-changing as a means of coping with high uncertainty. Second, this study demonstrates the understudied link between institutions and sensemaking by showing how professionals' embeddedness in their professional institution sets the focus of their sensemaking on the elements that support the institution. Third, these insights add to our knowledge of digitalization and professions by suggesting the potential high variability of professionals' strategies regarding digitalization due to their continuous updating of their view of the future, as well as the inherent antinomy of digitalization for established professions due to their advantaged but constrained position regarding digitalization.